2003
DOI: 10.1038/sj.bjp.0705329
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of potassium ion as the endothelium‐derived hyperpolarizing factor (EDHF) in the bovine coronary artery

Abstract: 1 This study explored the role of the potassium ion in endothelium-derived hyperpolarizing factor (EDHF)-mediated vasodilatation in the bovine coronary artery. 2 Bradykinin-induced, EDHF-mediated vasodilatation was blocked by the Na þ -K þ ATPase inhibitor, ouabain (1 mm), in a time-dependent manner, with maximal blockade seen after 90 min. In contrast, the K IR channel inhibitor, Ba 2 þ (30 mm), had no effect. 3 When the potassium content of the bathing solution was increased in a single step from 5.9 to 7 -1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 30 publications
0
19
0
1
Order By: Relevance
“…Edwards et al provided evidence that the targets of apamin and charybdotoxin are located on the endothelial cells, that potassium ions accumulate in the intercellular space between endothelial and smooth muscle cells, and that the potassium efflux associated with the activation of endothelial IK Ca and SK Ca channels produced hyperpolarization by activating both K IR and the Na + /K + pump on the smooth muscle cells. A role for the accumulation of K + ions in the intercellular space was then confirmed in many different arteries (145)(146)(147)(148)(149)(150)(151)(152). Nevertheless, this hypothesis has been highly controversial, possibly because the experimental conditions, and especially the presence or not of contractile agents, can markedly influence the contribution of K + ions in the overall mechanisms underlying endothelial-dependent hyperpolarizations.…”
Section: Beyond Endothelial Hyperpolarizationmentioning
confidence: 91%
“…Edwards et al provided evidence that the targets of apamin and charybdotoxin are located on the endothelial cells, that potassium ions accumulate in the intercellular space between endothelial and smooth muscle cells, and that the potassium efflux associated with the activation of endothelial IK Ca and SK Ca channels produced hyperpolarization by activating both K IR and the Na + /K + pump on the smooth muscle cells. A role for the accumulation of K + ions in the intercellular space was then confirmed in many different arteries (145)(146)(147)(148)(149)(150)(151)(152). Nevertheless, this hypothesis has been highly controversial, possibly because the experimental conditions, and especially the presence or not of contractile agents, can markedly influence the contribution of K + ions in the overall mechanisms underlying endothelial-dependent hyperpolarizations.…”
Section: Beyond Endothelial Hyperpolarizationmentioning
confidence: 91%
“…Since the original proposal that the diffusible EDHF in rat hepatic and mesenteric arteries was none other than the ionised K + ions that originated from activated endothelial cells [40], the hypothesis has received significant endorsement. Thus, K + signalling seems to play a key role not only in these rat vessels [36,43], but also in a variety of other bovine [97], human [20], murine [91], porcine [10] and rat [27] arteries. From a variety of methodological studies, the critical K IR channel is likely to be formed from a tetramer of K IR 2.1 α-subunits [17,39], while the Na + /K + -ATPase isoforms capable of responding to a raised [K + ] are those containing either the α2 or α3 subunits [12,39].…”
Section: Endothelial Cell-derived K + As An Edhfmentioning
confidence: 99%
“…Although the identity of EDHF has been the subject of considerable controversy [134], recent evidence suggests that EDHF is a K + ion, at least in hepatic, gastric, and cerebral arteries [14,75,85]. In addition, a number of reports have suggested that K + plays a role in the arterial response to EDHF [135][136][137], which involves the liberation of K + via endothelial Ca 2+ -activated K + channels with subsequently Kir2 channel activation, within the smooth muscle layer [84,89,138].…”
Section: Modulation Of Kir2 Channels By Edhf and Sodium Nitroprussidementioning
confidence: 98%